Frequently asked questions in corporate finance - Vernimmen, Pierre (Chichester, West Sussex ; Hoboken, N.J. : Wiley, 2011)
"This book draws on the invaluable content amassed by the vernimmen.com website and newsletters, and in the successful Vernimmen Corporate Finance book"--
Cover; Title Page; Copyright; Frequently Asked Questions; About the Authors; Chapter 1: Frequently Asked Questions; 1. What is Corporate Finance?; 2. What are Cash Flows?; 3. What Alternative Formats of the Balance Sheet May Companies Use?; 4. What is the Working Capital and How do Companies Manage It?; 5. What are the Alternative Formats of an Income Statement?; 6. How can We Perform the Financial Analysis of a Company?; 7. What is the Operating Profit?; 8. What is the Scissors Effect?; 9. How does Operating Leverage Work?; 10. What is CAPEX?
Includes index.
Includes bibliographical references and index.
Print version record.
Keywords: Corporations -- Finance; BUSINESS & ECONOMICS -- Accounting -- Managerial; BUSINESS & ECONOMICS -- Corporate Finance; BUSINESS & ECONOMICS -- Finance; Corporations -- Finance; Electronic books; Electronic books